Content Validity of PjBL Modules with a STEM-R Approach on the Topic of Renewable Energy for MTs Students - Mega Kurnia; Hamdi Akhsan; Ismet (Jurnal Pendidikan Fisika, 2026)
Science education in madrasahs requires modules that are scientifically sound and also integrated with Islamic values. However, the modules currently available generally do not systematically integrate the STEM-R approach, nor have they been validated through multidisciplinary assessment. This study aims to assess the content validity of PjBL STEM-R module on renewable energy topic for MTs students. The study uses a quantitative descriptive content validation, involving nine validators from three groups, namely science content experts, teacher practitioners, and religious experts. Data using a 1–5 Likert scale were analyzed using Aiken's V coefficient. The results showed an average Aiken's V of 0.90, with all components (content feasibility, PjBL, creative thinking, religious integration) categorized as Valid (V ≥ 0.83). The religious expert group gave the highest rating (0.92), confirming that the integration of Islamic values was carried out organically, contextually, and theologically appropriate. The findings prove that the module is suitable for use as teaching material that is valid in terms of content and context in a madrasah environment. This validation is an important foundation before wider implementation or testing of its effectiveness in improving students' creative thinking and religious attitudes.